2019
DOI: 10.21079/11681/33483
|View full text |Cite
|
Sign up to set email alerts
|

Ice control to prevent flooding in Ship Creek, Alaska

Abstract: ShipCreek is a steep, relatively small stream that flows through Joint Base Elmendorf-Richardson (JBER), Anchorage, Alaska. Ship Creek is a losing stream in its upper portion and a gaining stream in its lower portion, and this has significant impacts on the distribution of ice formation in the stream. Ice formation in Ship Creek is limited to the reach from roughly Vandenberg Avenue Bridge upstream to the Ship Creek Dam. This reach is steep with relatively high flow velocities. Anchor ice and ice dams form dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…This dam was put in place so that the City of Anchorage and the Joint Base Elmendorf-Richardson can pull drinking water from the river. There are no publicly available data on the amount of water withdrawn from the stream at this dam, but a U.S. Army Corps of Engineers study (Daly 2019) found that on average it is about 0.1 m 3 s −1 (2% of mean annual discharge). Finally, the Kenai River watershed has a hydroelectric dam that imports transboundary water.…”
Section: Study Area and Data Sourcesmentioning
confidence: 99%
“…This dam was put in place so that the City of Anchorage and the Joint Base Elmendorf-Richardson can pull drinking water from the river. There are no publicly available data on the amount of water withdrawn from the stream at this dam, but a U.S. Army Corps of Engineers study (Daly 2019) found that on average it is about 0.1 m 3 s −1 (2% of mean annual discharge). Finally, the Kenai River watershed has a hydroelectric dam that imports transboundary water.…”
Section: Study Area and Data Sourcesmentioning
confidence: 99%
“…Anchor ice dams are relatively rare and usually occur in steep, shallow rivers and streams (Rødtang et al 2021). In Alaska, a case study on Ship Creek near Anchorage, Alaska was completed in 2019 (Daly et al 2019) which analyzed the formation processes of anchor ice and anchor ice dams. Schematics in Figure 9 (A-D) show a systematic development of the typical ice dam process beginning with anchor ice formation along the bed (A) and progressing through increasingly greater ice accumulation on cobbles and boulders (B-C) until only a small subanchor ice channel is available for flow (D).…”
Section: Freeze-upmentioning
confidence: 99%
“…Schematics in Figure 9 (A-D) show a systematic development of the typical ice dam process beginning with anchor ice formation along the bed (A) and progressing through increasingly greater ice accumulation on cobbles and boulders (B-C) until only a small subanchor ice channel is available for flow (D). Anchor ice dams can result in significant upstream stage rise but are relatively short in duration since continued exposure to supercooled water is needed for the anchor ice to remain attached to the bottom of the river channel (Daly et al 2019;Kempema and Ettema 2011). Water intakes can experience significant problems with frazil ice if they are operated when the water is supercooled.…”
Section: Freeze-upmentioning
confidence: 99%